As marcas linguísticas da subjetividade: um estudo da singularidade enunciativa em fórum de discussão na EAD - Trindade, Charlene Oliveira (2016)
In this work, our purpose is to execute an enunciation study in the discussion forum on distance education. The general objective is verify how is constituted the subjective language marks from the tutor, in the distance education context , grounded by Enunciation Theory of Émile Benveniste (2005/2006) complemented with studies by Flores and Teixeira (2008), Fiorin (2005) and Maingueneau (1996). In this theoretical context, it was used as corpus the utterances from virtual learning environment of Undergraduate Course in Letters Portuguese and Literatures in the distance education modality, at Universidade Federal de Santa Maria, more specifically, the forum Artigo de opinião e carta aberta from the subject Gêneros e Leitura. The utterances of the tutors were analyzed and then confronted with the utterances of the subject professor, who released two video lessons in the virtual environment on the topic to be discussed at the forum. The analysis sought to confirm hypothesis that the distance education tutor is a person who repeats the statement of the other, but this tutor still shows its subjectivity; or that tutor is a person who conquers his place, but shows his views and modifies the professor‟ statement syntactically, but not semantically. The analysis was performed by verifying the enunciation marks more subjectivity obvious in utterances as one category, time and space, and in addition to other linguistic resources appointed by Benveniste (2006b) as accessories procedures in O Aparelho Formal da Enunciação. At the end of this study, we conclude that the distance education tutor, although his communication strategies, has an image of a teacher that promotes learning and motivates participation in the forum collaboratively, however, this tutor is a mediator who needs the professor speech to support his discourse